State-society Interactions and Bordering Practices in Gurugram's Pandemic Response. (November 2020) - Naik, Mukta
Civil society has played a key role in responding to the COVID-19 crisis in Indian cities. This article uses the conceptualisation of boundaries and borders to reflect on the role of local state and civil society actors in Gurugram's pandemic response. It examines the state's bordering practices, state-society relations as well as processes of negotiation that enabled disease management as well as relief efforts-especially for migrant workers-during the crisis.